The Influence of Marketing Mix and Brand Image on Repurchase Intention and Consumer Satisfaction: Study at Kampung Pempek 26 Ilir Palembang - Rika Carolina (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2024)
This study examines the influence of the marketing mix and brand image on consumer satisfaction and repurchase intention in Kampung Pempek 26 Ilir, a designated center for purchasing pempek and souvenirs in Palembang. The research aims to identify key factors that drive repeat visits and improve sales for this tourism and culinary destination. A quantitative approach with descriptive analysis was utilized, targeting residents of Palembang who have visited Kampung Pempek 26 Ilir. A total of 210 respondents were selected using accidental sampling. Data analysis measured the direct and mediated effects of the marketing mix and brand image on consumer satisfaction and repurchase intention. The marketing mix showed a positive and significant influence on repurchase intentions and consumer satisfaction. When mediated by consumer satisfaction, the marketing mix had an additional positive effect on repurchase intention. Brand image also significantly influenced repurchase intention and consumer satisfaction. Findings suggest that both the marketing mix and brand image are crucial in enhancing consumer satisfaction and encouraging repeat visits to Kampung Pempek 26 Ilir. The positive mediation effects of consumer satisfaction indicate its role as an essential bridge between marketing strategies and consumer loyalty. The study concludes that improving both the marketing mix and brand image can substantially enhance consumer satisfaction and repurchase intention. Specifically, consumer satisfaction is a pivotal factor in increasing consumer loyalty and the likelihood of repeat purchases. The recommendation for Kampung Pempek 26 Ilir is to invest in optimizing its marketing strategies and brand image to enhance consumer satisfaction. Further studies could explore additional factors that influence consumer loyalty in similar cultural and culinary tourism centers.